若a-b=(5√2)-1,ab=√2,求(a+b)(a-b)的值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 02:16:03
若a-b=(5√2)-1,ab=√2,求(a+b)(a-b)的值若a-b=(5√2)-1,ab=√2,求(a+b)(a-b)的值若a-b=(5√2)-1,ab=√2,求(a+b)(a-b)的值(a-b
若a-b=(5√2)-1,ab=√2,求(a+b)(a-b)的值
若a-b=(5√2)-1,ab=√2,求(a+b)(a-b)的值
若a-b=(5√2)-1,ab=√2,求(a+b)(a-b)的值
(a-b)^2=(a+b)^2-4ab
a+b=√[50+1-10√2+4√2]=√(51-6√2)
(a+b)(a-b)=(5√2-1)√(51-6√2)
若a-b=(5√2)-1,ab=√2,求(a+b)(a-b)的值
已知a-2√ab+b=0(a>0,b>0),求(3a-√ab+b)/(5a+3√ab-4b)的值
a(a-1)-(a×a-b)=-5,求(a×a+b×b)÷2-ab
若a+b=3,ab=-2,求(5a-5b-ab)-(4a-6b-3ab)
ab为实数√a-5+2√10-2a=b+4求ab
已知ab^2=-1,求-ab(a^2b^5-ab^3-b)的值
已知a-b=2,ab=-1 求(4a-5b-ab)-(2a-3b-5ab)
1.已知a=2+√3b=2-√3求:((√ab)+(ab/(a-2√ab)))/((2√ab-b)/(a-b))注:√ab都是根号下ab2.若a、b为有理数,(a+√3)*(a+√3)=b-8√3求:a-b3.a+b=2√(ab)a大于0,b大于0求√(a+b)与√(3a+5b
已知a,b满足a+b=5,a-b=1,求ab,a^2+b^2-3ab
若(a+b)+|b+1|=0求5ab²-[3ab²-(4ab²-2a²b)}+2a²b
若a-b=4,ab=1,求(-2ab+2a+3b)-(3ab+2b-2a)-(a+4b+ab)的值
若a-b=4 ab=1 求(-2ab+2a+3b)-(3ab+2b-2a)-(a+4b+ab)的值
若a-b=4 ab=1 求(-2ab+2a+3b)-(3ab+2b-2a)-(a+4b+ab)的值
已知a-b=5,ab=-1,求(3b+a-2ab)-2(b-3.5a-ab)+3(ab+2a-5b)的值
已知a-b=5,ab=-1,求(2a+3b-2ab)-(a+4b+ab)-(3ab+2b-2a)的值
a-b=5 ab=--1求(2a+3b-2ab)-(a+4b+ab)-(3ab-2a+2b)的值
已知a-b=5,ab=-1,求代数式(22a+3b-2ab)-(a+4b+ab)-(3ab+2b-2a)的值.
若ab^2+1=0,用因式分解法求-ab(a^2b^5-ab^3-b)